Vibration influence on mechanical properties of castings - Kovač, Risto; Jojin, Siniša (Journal of Production Engineering, 1989)
This paper presents an investigation into the influence of vibration, specifically its amplitude and frequency, on the hardness of castings made from AlCu4.5 alloy. The castings were subjected to vibration during the solidification process. The results of the investigation indicate that vibrating the castings increases their hardness, with frequency having a more significant influence.